PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASAN KERJA: Studi pada driver PT. Go To Gojek Tokopedia - Meita Pragiwani; Benny Alexandri; Farmansjah Maliki; Muajalah Muajalah (Jurnal Ilmiah Magister Ilmu Administrasi, 2023)
The purpose of this research is to know and understand and analyze the influence of work discipline, work environment and occupational safety and health on the job satisfaction of Gojek Drivers. This study uses a quantitative method that is descriptive and associative. The population of this study is motorcycle taxi drivers. The sample collection technique uses the purposive sampling method, with a total sample of 75 drivers. The data collection technique uses a questionnaire that has been tested for validity and reliability. The analysis used is the coefficient of determination using SPSS version 24.0. The results showed that the work discipline variable had a positive and insignificant effect on job satisfaction, for work environment variables it had a positive and insignificant effect on job satisfaction, in contrast to occupational safety and health it had a positive and significant effect on driver job satisfaction, simultaneously work discipline , work environment and occupational health and safety affect job satisfaction